Vaižgantas’s Attempts at Constructing Lithuanian Collective Memory - Mačiulis, Dangiras (Colloquia, 2020)
By analyzing the written legacy of Juozas Tumas-Vaižgantas, the author of the article discusses his activities in forming Lithuanian collective memory. He argues that Vaižgantas‘s point of view towards the importance of collective memory in the life of the Lithuanian people has changed under the influence of political circumstances. Up until WWI, Vaižgantas thought that in order to consolidate the Lithuanian national community, the mother tongue would serve better than constructing collective memory by ways of reminding Lithuanians of the heroic episodes of their country‘s history. During the WWI, in his attempts at validating the right of Lithuanians to political and cultural emancipation, Vaižgantas began using the images of the Grand Duchy of Lithuania which were reminiscent of the Lithuanian historical statehood. In the late 1920s, Vaižgantas actively participated in the organization of the jubilee campaign of remembrance of the Grand Duke of Lithuania, Vytautas the Great (1350-1430). He believed that the actualization of the memory of the statehood of the GDL, symbolized by the personality of Vytautas the Great, could help to highlight the tradition of Lithuanian historical statehood and cultural continuity.